2017
DOI: 10.3389/fmicb.2017.00452
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Energy Budgets of Phototrophic Surface-Associated Microbial Communities and their Photosynthetic Efficiency Under Diffuse and Collimated Light

Abstract: We investigated the radiative energy budgets of a heterogeneous photosynthetic coral reef sediment and a compact uniform cyanobacterial biofilm on top of coastal sediment. By combining electrochemical, thermocouple and fiber-optic microsensor measurements of O2, temperature and light, we could calculate the proportion of the absorbed light energy that was either dissipated as heat or conserved by photosynthesis. We show, across a range of different incident light regimes, that such radiative energy budgets are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…Corals are counted among the most efficient aquat ic photosynthetic organisms (Al-Najjar et al 2010, Brodersen et al 2014, Lichtenberg et al 2017, and the high photosynthetic activity of P. damicornis observed here and in Lyndby et al (2019) supports that notion. However, carbon energy budgets established here show evidence that a large fraction of assimilated carbon is lost quickly, either as respiration or released as dissolved inorganic carbon, in agreement with a previous study on energy and carbon dynamics in P. eydouxi (Davies 1984).…”
Section: Discussionsupporting
confidence: 66%
“…Corals are counted among the most efficient aquat ic photosynthetic organisms (Al-Najjar et al 2010, Brodersen et al 2014, Lichtenberg et al 2017, and the high photosynthetic activity of P. damicornis observed here and in Lyndby et al (2019) supports that notion. However, carbon energy budgets established here show evidence that a large fraction of assimilated carbon is lost quickly, either as respiration or released as dissolved inorganic carbon, in agreement with a previous study on energy and carbon dynamics in P. eydouxi (Davies 1984).…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, studies on energy use efficiency in other highly pigmented photosynthetic systems (e.g. benthic biofilms and coral sediments) reveal low energy use efficiencies due to their more uniform topography and high optical density (Al-Najjar et al 2010, Lichtenberg et al 2017.…”
Section: Radiative Energy Budgetsmentioning
confidence: 95%
“…Studies of photosynthetic efficiency and radiative energy budgets accounting for the fate of incident and absorbed light energy in benthic marine systems have so far focused on sediments, biofilms, and microbial mats (Al-Najjar et al 2010, Lichtenberg et al 2017, with the exception of a single study on a symbiont-bearing coral showing that light is used very efficiently for photosynthesis in corals (Brodersen et al 2014). It was found that while the majority (> 96%) of incident light energy was absorbed and dissipated as heat, the local photosynthetic energy efficiency of zooxanthellae in the tissue of corals measured under low to moderate irradiance approached the theoretical maximum of 0.125 mol O 2 per mol photons.…”
Section: Open Pen Access Ccess Feature Articlementioning
confidence: 99%
“…It is interesting to note that the thickness of the active biofilm (defined as the area where the photosynthesis rate is larger than 1% of its maximal) reaches a constant value of 75 ± 7.5 μ m after 5 days. This means that the superficial layers of the biofilm are the most photosynthetically active, as supported by several experimental studies on phototrophic biofilms [ 43 45 ]. Typically, the factor driving the vertical distribution of the active layers in photosynthetic biofilms is light, which is imposing the extent of the euphotic zone [ 43 ].…”
Section: Resultsmentioning
confidence: 77%